Hospital at Home admission avoidance with comprehensive geriatric assessment to maintain living at home for people aged 65 years and over: a RCT - Shepperd, S; Cradduck-Bamford, A; Butler, C; Ellis, G; Godfrey, M; Gray, A; Hemsley, A; Khanna, P; Langhorne, P; Mäkelä, P; Mort, S; Ramsay, S; et al. (National Institute for Health Research, 2022)
Background Evidence is required to guide the redesign of health care for older people who require hospital admission. Objectives We assessed the clinical effectiveness and cost-effectiveness of geriatrician-led admission avoidance hospital at home with comprehensive geriatric assessment, the experiences of older people and their caregivers, and how the services differed. Design A multisite, randomised, open trial of comprehensive geriatric assessment hospital at home, compared with admission to hospital, using a 2 : 1 (hospital at home to hospital) ratio, and a parallel economic and process evaluation. Participants were randomised using a secure online system. Setting Participants were recruited from primary care or acute hospital assessment units from nine sites across the UK. Participants Older people who required hospital admission because of an acute change in health. Intervention Geriatrician-led admission avoidance hospital at home with comprehensive geriatric assessment. Main outcome measures The main outcome, ‘living at home’ (the inverse of death or living in a residential care setting), was measured at 6-month follow-up. Secondary outcomes at 6 months were the incidence of delirium, mortality, new long-term residential care, cognitive impairment, ability to perform activities of daily living, quality-adjusted survival, length of stay and transfer to hospital. Secondary outcomes at 12 months were living at home, new long-term residential care and mortality. Results Participants were allocated to hospital at home (n = 700) or to hospital (n = 355). All reported relative risks (RRs) were adjusted and are reported for hospital at home compared with hospital. There were no significant differences between the groups in the proportions of patients ‘living at home’ at 6 months [528/672 (78.6%) vs. 247/328 (75.3%), RR 1.05, 95% confidence interval (CI) 0.95 to 1.15; p = 0.36] or at 12 months [443/670 (66.1%) vs. 219/325 (67.4%), RR 0.99, 95% CI 0.89 to 1.10; p = 0.80]; mortality at 6 months [114/673 (16.9%) vs. 58/328 (17.7%), RR 0.98, 95% CI 0.65 to 1.47; p = 0.92] or at 12 months [188/670 (28.1%) vs. 82/325 (25.2%), RR 1.14, 95% CI 0.80 to 1.62]; the proportion of patients with cognitive impairment [273/407 (67.1%) vs. 115/183 (62.8%), RR 1.06, 95% CI 0.93 to 1.21; p = 0.36]; or in ability to perform the activities of daily living as measured by the Barthel Index (mean difference 0.24, 95% CI –0.33 to 0.80; p = 0.411; hospital at home, n = 521 patients contributed data; hospital, n = 256 patients contributed data) or Comorbidity Index (adjusted mean difference 0.0002, 95% CI –0.15 to 0.15; p = 0.10; hospital at home, n = 474 patients contributed data; hospital, n = 227 patients contributed data) at 6 months. The varying denominator reflects the number of participants who contributed data to the different outcomes. There was a significant reduction in the RR of living in residential care at 6 months [37/646 (5.7%) vs. 27/311 (8.7%), RR 0.58, 95% CI 0.45 to 0.76; p < 0.001] and 12 months [39/646 (6.0%) vs. 27/311 (8.7%), RR 0.61, 95% CI 0.46 to 0.82; p < 0.001], a significant reduction in risk of delirium at 1 month [10/602 (1.7%) vs. 13/295 (4.4%), RR 0.38, 95% CI 0.19 to 0.76; p = 0.006] and an increased risk of transfer to hospital at 1 month [173/672 (25.7%) vs. 64/330 (19.4%), RR 1.32, 95% CI 1.06 to 1.64; p = 0.012], but not at 6 months [343/631 (54.40%) vs. 171/302 (56.6%), RR 0.95, 95% CI 0.86 to 1.06; p = 0.40]. Patient satisfaction was in favour of hospital at home. An unexpected adverse event that might have been related to the research was reported to the Research Ethics Committee. At 6 months, there was a mean difference in NHS, personal social care and informal care costs (mean difference –£3017, 95% CI –£5765 to –£269), and no difference in quality-adjusted survival. Older people and caregivers played a crucial role in supporting the delivery of health care. In hospital at home this included monitoring a patient’s health and managing transitional care arrangements. Limitations The findings are most applicable to patients referred from an acute hospital assessment unit. Conclusions Comprehensive geriatric assessment hospital at home can provide a cost-effective alternative to hospitalisation for selected older people. Further research that includes a stronger element of carer support might generate evidence to improve health outcomes. Trial registration This trial is registered as ISRCTN60477865.